Assessing the Threat and Vulnerability of Hallyu among Indonesian Generation Z - Ria AS (Security Intelligence Terrorism Journal (SITJ), 2026)
Hallyu, or the Korean Wave, has evolved into a global cultural phenomenon that shapes consumption patterns, identity formation, and lifestyle orientations across national boundaries. In Indonesia, the extensive exposure of Generation Z to Korean popular culture through digital platforms positions this cohort as a strategically significant audience within transnational cultural flows. This study examines the threat and vulnerability of Hallyu exposure among Indonesian Generation Z and examines its implications for cultural resilience in a rapidly globalizing cultural environment. Employing a qualitative descriptive analytical approach, the study draws on non participatory observation, semi structured interviews with institutional stakeholders, cultural actors, and youth communities, and analysis of official cultural documents. Data were interpreted using Prunckun’s threat and vulnerability assessment framework and an intelligence informed analytical perspective. The findings indicate a moderate threat level with a total threat coefficient of 13, driven primarily by high capability factors, particularly knowledge and resource mobilization supporting Hallyu dissemination. The vulnerability assessment yields a moderate vulnerability profile (coefficient score: 9), reflecting strong attractiveness, facilitated digital penetration, and cumulative cultural impact. The study argues that Hallyu constitutes an invisible cultural security challenge that does not manifest through coercion, but through gradual normalization and asymmetry in cultural influence. Strengthening cultural resilience through governance, literacy, and competitive local cultural ecosystems is therefore essential to ensure balanced cultural development without securitizing popular cultural consumption.